Shape memory properties of epoxy with hybrid multi-walled carbon nanotube and montmorillonite nanoclay nanofiller - Mat Yazik, Muhamad Hasfanizaam; Hameed Sultan, Mohamed Thariq; Jawaid, Mohammad; Mazlan, Norkhairunnisa; Abu Talib, Abd Rahim; Md Shah, Ain Umaira; Safri, Syafiqah Nur Azrie (Springer, 2024)
The shape memory epoxy polymer (SMEP) nanocomposite incorporated with hybrid of multi-walled carbon nanotube (MWCNT) and montmorillonite nanoclay (MMT) was studied in terms of shape memory properties. The SMEP nanocomposites were characterised via cyclic thermomechanical test and fold-deploy test. The inclusion of hybrid nanofiller shows decrease in shape recovery except for SMEP nanocomposite. The recovery via thermal and electrically activated recovery shows similar recovery profile although electrically activated recovery reacts faster than thermally activated recovery. However, the effect of nanofiller inclusion is more prominent on the thermal activation method. Hybrid filler SMEP nanocomposite with 3 wt. MMT and 1.0 wt. MWCNT has better shape memory properties than other nanocomposites being studied. This can be attributed to better dispersion and synergetic effect of hybridisation between the nanofillers. These findings can be a guideline to initial selection of nanofiller loadings based on performance for specific application in various industries such as aerospace, medical and automotive.